Endometriosis Toraks di Diafragma Dextra dengan Manifestasi Nyeri Dada dan Pneumotoraks - Tommy Dharmawan; Tania Maharani Chandra; Andon Hestiantoro; Agnes Stephanie Harahap (Majalah Kedokteran Indonesia, 2023)
Introduction: Thoracic endometriosis is a rare disease but could lead to morbidity and mortality. Early detection with prompt anamnesis and supporting examination may direct the best therapy and also increase the prognosis of patient.Case report: On this case report, we presented a female patient with right chest pain and shortness of breath on menstruation time.Discussion: From chest X-ray we found right pneumothorax and it led to chest tube placement on the right chest. The anamnesis supported the diagnosis of thoracic endometriosis and furthermore from CT scan we found lesion on the right diaphragm. So, we proceeded with minimal invasive surgery (video assisted thoracoscopic surgery (VATS)). Pathology anatomy examination revealed a true endometriosis lesion.Conclusion: The operation went uneventful and then post operative we gave gonadotropin releasing hormone analog.